2022
DOI: 10.3847/1538-4357/ac7443
|View full text |Cite
|
Sign up to set email alerts
|

Spectra of Cosmic-Ray Sodium and Aluminum and Unexpected Aluminum Excess

Abstract: Since its launch, the Alpha Magnetic Spectrometer-02 (AMS-02) has delivered outstanding quality measurements of the spectra of cosmic-ray (CR) species, p ¯ , e ±, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 55 publications
(111 reference statements)
1
7
0
Order By: Relevance
“…predictions in some peculiar rigidity windows: contributions of local new sources are most likely. The WR hypothesis, that was invoked to reproduce the observed isotopic ratios ( 22 Ne/ 20 Ne, 12 C/ 16 O and 58 Fe/ 56 Fe), could be also consistent with the observed excesses in Li, F and Al, while excess in primary Fe should be connected with a past SN activity few Myr ago in the Local Bubble. Absence of a corresponding signal in sodium supports this scenario.…”
Section: Discussionsupporting
confidence: 77%
See 4 more Smart Citations
“…predictions in some peculiar rigidity windows: contributions of local new sources are most likely. The WR hypothesis, that was invoked to reproduce the observed isotopic ratios ( 22 Ne/ 20 Ne, 12 C/ 16 O and 58 Fe/ 56 Fe), could be also consistent with the observed excesses in Li, F and Al, while excess in primary Fe should be connected with a past SN activity few Myr ago in the Local Bubble. Absence of a corresponding signal in sodium supports this scenario.…”
Section: Discussionsupporting
confidence: 77%
“…In particular, exploiting several of the most recent high quality AMS-02 results, we found that some CR ions still seem to require an additional primary component in some rigidity windows: they are lithium [2], iron [5], fluorine [6] and aluminum [7]. See [12,18,19,20] for insights and details.…”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations